Adaptive capacity of small‐scale coastal fishers to climate and non‐climate stressors in the Western region of Ghana. Issue 1 (22nd October 2018) - Freduah, George; Fidelman, Pedro; Smith, Timothy F.
Abstract : Small‐scale coastal fisheries (SSCF) in the Western region of Ghana are affected by a combination of climate and non‐climate stressors. Coastal communities are particularly vulnerable to these stressors because of their proximity to the sea and high dependence on small‐scale fisheries for their livelihoods. A better understanding of how fishing communities, particularly SSCF, respond to climate and non‐climate stressors is paramount to improve planning and implementation of effective adaptation action. Drawing on the capitals framework, this study examines the adaptive capacity of SSCF to the combined effects of climate‐related (increasing coastal erosion, and wave and storm frequency) and non‐climate‐related stressors (declining catches; scarcity and prohibitive cost of fuel; inconsiderate implementation of fisheries laws and policies; competition from the oil and gas industry; sand mining; and algal blooms). The findings show how fishers mobilise and use adaptive capacity through exploitation of various forms of capital, including cultural capital (e.g., local innovation); political capital (e.g., lobbying government and local authorities); social capital (e.g., collective action); human capital (e.g., local leadership); and natural capital (e.g., utilising beach sand) to respond to multiple stressors. Nevertheless, in many cases, fishers' responses were reactive and led to negative (maladaptive) outcomes. Furthermore, this study underscores the importance of critically considering the interactive nature of capitals and how they collectively influence adaptive capacity in the planning and implementation of adaptation research, policy and practice. Abstract : This study draws on the capitals framework to examine the adaptive capacity of Small‐scale coastal fisheries (SSCF) in the Western Region of Ghana to the combined effects of climate‐related and non‐climate related stressors. Findings show fishers have a low adaptive capacity and, in many cases, their responses are reactive and lead to negative (maladaptive) outcomes.